Syndecans in skeletal muscle development, regeneration and homeostasis - Pisconti, Addolorata (CIC Edizioni Internazionali, 2012)
Skeletal muscle is a highly dynamic tissue that can change in size in response to physiological demands and undergo successful regeneration even upon extensive injury. A population of resident stem cells, termed satellite cells, accounts for skeletal muscle plasticity, maintenance and regeneration. Mammalian satellite cells, generated from muscle precursor cells during development, are maintained quiescent in the musculature throughout a lifespan, but ready to activate, proliferate and differentiate into myocytes upon demand. Syndecans are transmembrane heparan sulfate proteoglycans expressed in muscle precursors during embryonic development and in satellite cells during postnatal life. In the last decades a number of crucial functions for syndecans in myogenesis and muscle disease have been described. Here we review the current knowledge of the multiple roles played by syndecans in the skeletal muscle of several animal models and explore future perspectives for human muscle health, with a focus on muscle aging and muscular dystrophy.